Inhibition of Staphylococcus pseudintermedius Efflux Pumps by Using Staphylococcus aureus NorA Efflux Pump Inhibitors - Elisa Rampacci; Tommaso Felicetti; Giada Cernicchi; Valentina Stefanetti; Stefano Sabatini; Fabrizio Passamonti (MDPI AG, 2023)
One promising approach in treating antibiotic-resistant bacteria is to "break" resistances connected with antibacterial efflux by co-administering efflux pump inhibitors (EPIs) with antibiotics. Here, ten compounds, previously optimized to restore the susceptibility to ciprofloxacin (CIP) of norA-overexpressing Staphylococcus aureus, were evaluated for their ability to inhibit norA-mediated efflux in Staphylococcus pseudintermedius and synergize with CIP, ethidium bromide (EtBr), gentamycin (GEN), and chlorhexidine digluconate (CHX). We focused efforts on S. pseudintermedius as a pathogenic bacterium of concern within veterinary and human medicine. By combining data from checkerboard assays and EtBr efflux inhibition experiments, the hits 2-arylquinoline 1, dihydropyridine 6, and 2-phenyl-4-carboxy-quinoline 8 were considered the best EPIs for S. pseudintermedius. Overall, most of the compounds, except for 2-arylquinoline compound 2, were able to fully restore the susceptibility of S. pseudintermedius to CIP and synergize with GEN as well, while the synergistic effect with CHX was less significant and often did not show a dose-dependent effect. These are valuable data for medicinal chemistry optimization of EPIs for S. pseudintermedius and lay the foundation for further studies on successful EPIs to treat staphylococcal infections.